2015
DOI: 10.1111/lam.12429
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time loop-mediated isothermal amplification assay for the sensitive and rapid detection of Listeria monocytogenes

Abstract: Conventional culture and molecular detection methods are always time consuming and require a specific laboratory infrastructure, thereby restricting their use for the rapid detection and diagnosis of pathogens. A real-time loop-mediated isothermal amplification (RealAmp) assay performed by ESEtube scanner to rapidly detect Listeria monocytogenes isolated from food was developed. The results showed that the RealAmp assay using the tube scanner was more efficient and precise than the conventional API Listeria as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The LAMP assay was revealed to have a similar limit of detection in pasteurized cow milk and pure culture. Comparing this to the existing literature, 2 studies have previously reported that the results produced from the LAMP assay in detecting P. fluorescens in pure culture and in artificially contaminated milk samples were of a similar order of magnitude (Cho et al, 2014;Ye et al, 2015). Three out of 5 published studies have suggested that the detection limit of the method is lower in pure culture than in milk (Yang et al, 2011;Wang et al, 2015;Cornelissen et al, 2016).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The LAMP assay was revealed to have a similar limit of detection in pasteurized cow milk and pure culture. Comparing this to the existing literature, 2 studies have previously reported that the results produced from the LAMP assay in detecting P. fluorescens in pure culture and in artificially contaminated milk samples were of a similar order of magnitude (Cho et al, 2014;Ye et al, 2015). Three out of 5 published studies have suggested that the detection limit of the method is lower in pure culture than in milk (Yang et al, 2011;Wang et al, 2015;Cornelissen et al, 2016).…”
Section: Discussionsupporting
confidence: 51%
“…Portable fluorescence detectors have already been applied to on-site detection of microorganisms and have been shown to deliver the same results as fluorescence quantification PCR instruments (Fu et al, 2016). Moreover, a battery-operated portable fluorescence detector can be used in conjunction with the LAMP assay system (Ye et al, 2015;Lee et al, 2016). Furthermore, because the LAMP reaction tubes are not opened until the reaction has completed, the potential risks of cross-contamination and false- ; lanes 1, 2, 3, 4, 5, 6, and 7 represent 4.8 × 10 5 , 4.8 × 10 4 , 4.8 × 10 3 , 4.8 × 10 2 , 4.8 × 10 1 , 4.8 × 10 0 , and 4.8 × 10 −1 cfu/reaction, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It was highly specific to L. monocytogenes and was able to detect as low as 1 CFU of the bacterium per reaction (50 µl) without DNA purification, or 100 fg of the genomic DNA/50 µl. This sensitivity was higher than the LAMP testing limit of 10 3 CFU/ml and was comparable to the detection limit of PCR-or qPCR-based methods, which was between 10 2 and 10 3 CFU/ml (Ye et al, 2015;Jayanth and Varadaraj, 2017;Garrido-Maestu et al, 2018). The amplification could be conducted under the temperature between 37 and 42 • C, and the whole detection finished within 25 min.…”
Section: Application Of the Rpa-lfs System For L Monocytogenes Detecmentioning
confidence: 81%
“…Compared with real-time PCR method, RealAmp has the improved specificity and sensitivity. Ye et al ( 2015 ) compared RealAmp with the API Listeria and real-time PCR assays to detect Listeria . All 58 L. monocytogenes strains from different countries were detected by the RealAmp assay, whereas only 57 (98.3%) and 56 (96.6%) strains were identified as L. monocytogenes by the API Listeria and PCR assays respectively, thereby demonstrating that it has a higher specificity and sensitivity than conventional identification assays.…”
Section: Lamp In Food Microbial Detectionmentioning
confidence: 99%